Pengaruh Kualitas Pelayanan dan Motivasi Terhadap Minat Kunjung Wisatawan pada Jeep Lava Tour Merapi - Pratama, Doni; Nusanto, Tri Suyud; Prasetyo, Danang (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
This research describes and analyzes the influence of service quality and motivation on tourists' interest in visiting the Merapi Jeep Lava Tour, using a quantitative method. This study collected data through the distribution of questionnaires to visitors who visited the Merapi Lava Tour. The results of this research explain that service quality and motivation have a significant influence on tourists' interest in visiting. The conclusion of this research confirms that service quality and motivation have a positive influence on tourists' interest in visiting. Suggestions given involve maintaining service quality, innovating attractions to attract more tourists who want to visit.